Effect of superovulation on ovarian response and subsquent embryo transfer in goats / Shariffah binti Nazari - Nazari, Shariffah (2013)
This study was conducted to evaluate the effects of oFSH dosages on ovarian responses during superovulation treatment. A total of 35 mature crossbred goats were synchronised for oestrus with CIDR devices for a period of 13 days. The does were divided into 3 groups, namely groups M1, M2 and S receiving 8.8 mg and 14.1 mg of oFSH through multiple intramuscular (i.m.) injection starting from 2 days before the CIDR removal and 8.8 mg of oFSH through single i.m. injection upon CIDR removal, respectively. Ovarian responses of all treatments were evaluated during laparotomy session on days 3 or 7 after CIDR removal. All the does of group M1 (100%, 13/13) and M2 (100%, 9/9) responded to the treatments with at least 3 corpus luteum (CL). On the other hand, only 69% (9/13) of the does of group S responded corresponding to the treatment. The total ovarian responses (CL plus anovulatory follicles) among the treatments were significantly (P<0.05) higher in multiple administration groups (groups M1 and M2) than the single administration group (group S). Although no significant (P>0.05) differences were found between multiple administration groups for ovarian responses, high dosage of oFSH consistently gave higher percent ovulation and CL per doe (72.4% ± 7.6 vs. 58.8% ± 3.9 and 16.9 ± 3.9 vs. 11.6 ± 1.0, respectively) compared to low dosage. The anovulatory percentage of follicles was significantly (P<0.05) higher in group S followed by groups M1 and M2. The structure (embryo plus oocyte) recovery rate per doe was significantly (P<0.05) higher in group M2 followed by group M1 and group S (5.4 ± 2.4, 3.2 ± 1.2 and 0.5 ± 0.5, respectively). However, no significant difference (P<0.05) in the number of viable embryo in multiple administration groups (M1; 2.4 ± 1.0, M2; 2.0 ± 1.4, respectively) and single administration group (S; 0.1 ± 0.1). It is concluded that in multiple injection of oFSH superovulation protocol, the total dosage, breed and body weight have no effect on production of viable embryos in common goat genotype in Malaysia. Low total dosage administered in multiple injections is economically advantageous and convenient for the production of competent in vivo embryos. However, more detailed research is needed to optimise the amount of gonadotrophin for superovulation of Malaysian crossbred goats.